2015
DOI: 10.1038/ncomms8184
|View full text |Cite
|
Sign up to set email alerts
|

Loss of polarity protein AF6 promotes pancreatic cancer metastasis by inducing Snail expression

Abstract: Pancreatic cancer (PC) is a particularly lethal form of cancer with high potential for metastasis to distant organs. Disruption of cell polarity is a hallmark of advanced epithelial tumours. Here we show that the polarity protein AF6 (afadin and MLLT4) is expressed at low levels in PC. We demonstrate that depletion of AF6 markedly promotes proliferation and metastasis of PC cells through upregulation of the expression of Snail protein, and this requires the nuclear localization of AF6. Furthermore, AF6 deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 45 publications
2
65
0
Order By: Relevance
“…Recent work has established a direct connection between low levels of afadin and tumor growth in different cancer types (Fournier et al, 2011;Xu et al, 2015). Intriguingly, both Cno and afadin bind the activated form of Ras (Ras-GTP), RAS being one of the most commonly mutated oncogenes in human cancers, and we showed some years ago that Cno represses Ras during the specification of Drosophila muscle and heart progenitors (Carmena et al, 2006;Kuriyama et al, 1996).…”
Section: Discussionmentioning
confidence: 79%
“…Recent work has established a direct connection between low levels of afadin and tumor growth in different cancer types (Fournier et al, 2011;Xu et al, 2015). Intriguingly, both Cno and afadin bind the activated form of Ras (Ras-GTP), RAS being one of the most commonly mutated oncogenes in human cancers, and we showed some years ago that Cno represses Ras during the specification of Drosophila muscle and heart progenitors (Carmena et al, 2006;Kuriyama et al, 1996).…”
Section: Discussionmentioning
confidence: 79%
“…The supernatant was recovered and protein concentration was determined by the Bio-Rad protein assay kit (Hercules, CA) according to the manufacturer's instructions. Western blot assays were performed as previously described [13]. The primary antibodies were obtained as follows: anti-SORBS1, anti-GAPDH, and anti-β-actin antibody from Abmart; anti-Hsp90, anti-Snail, anti-Slug, anti-vimentin, anti-JNK, anti-p-JNK, anti-c-Jun, anti-p-c-Jun, anti-p53, anti-caspase3, and anti-cleaved-caspase3 antibodies and horseradish peroxidase (HRP) -conjugated secondary antibodies from Cell Signaling Technology; and anti-E-cadherin and anti-N-cadherin antibodies from BD Transduction Laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several reports revealed that filopodium-like protrusions (FLPs) can facilitate the proliferation of cancer cells that infiltrate into the parenchyma of foreign tissues following egress from the primary site [4, 7]. Furthermore, research on the underlying molecular mechanisms demonstrate that both adhesion molecules (for example, E-cadherin [8, 9], N-cadherin [9], vimentin [10] and integrins [11]) and adaptor proteins (for example, vinculin [12], afadin [13], paxillin [14], Grb2 [15], and ArgBP2 [16]) have effects on invasion and metastasis via changes in actin cytoskeleton, cell-cell/ECM adhesions, or EMT. Although the basic knowledge related to this process has been explored for long time, the underlying key elements are largely unknown and the functions of many suspected regulators remain to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…1). The poor prognosis in PDAC is primarily due to early onset of distant metastasis234. Understanding the mechanisms that regulate PDAC metastasis are critical to improving PDAC treatment.…”
mentioning
confidence: 99%